Pengaruh Kualitas Interpretasi Terhadap Kepuasan Dan Persepsi Wisatawan Di Tjong A Fie - Vidya Amanda; Cece (Management of Information System Journal, 2026)
This study is motivated by the importance of the quality of tour guides’ interpretations in building a positive destination image and enhancing the satisfaction of tourists visiting Tjong A Fie in Medan. The objective of this study is to analyze the influence of the quality of historical interpretations provided on tourists’ satisfaction and positive perspectives regarding their visit. This study employs a quantitative method with descriptive and causal approaches. Data collection was conducted through the distribution of questionnaires to 100 respondents. This study utilizes the Partial Least Squares –Structural Equation Modeling (PLS–SEM) technique with the assistance of SmartPLS software. The results of this study indicate that historical interpretation has a positive and significant effect on tourist satisfaction, with a t- statistic of 11.82 and a p-value of 0.000. This study also shows a positive relationship between the quality of interpretation and tourist perceptions, with a t-statistic of 3.478 and a p-value of 0.001. This study concludes that there is a positive influence between the quality of historical interpretation and tourist satisfaction and perception. This study demonstrates that improving the quality of historical narratives and guide communication is the key to sustaining the intellectual aspect of historical tourism.